The Cambridge history of philosophy in the nineteenth century (1790-1870) - Wood, Allen W.; Hahn, Songsuk Susan (Cambridge : Cambridge University Press, 2012)
'The latest volume in the Cambridge Histories of Philosophy series, The Cambridge History of Philosophy in the Nineteenth Century brings together twenty-nine leading experts in the field and covers the years 1790-1870. Their twenty-seven chapters provide a comprehensive survey of the period, organizing the material topically. After a brief editor's introduction, it begins with three chapters surveying the background of nineteenth century philosophy: followed by two on logic and mathematics, two on nature and natural science, five on mind and language, including psychology, the human sciences and aesthetics, four on ethics, three on religion, seven on society, including chapters on the French Revolution, the decline of natural right, political economy, and social discontent, and three on history, dealing with historical method, speculative theories of history and the history of philosophy. The essays are framed by an editor's introduction and a bibliography'--
Includes bibliographical references (p. 905-956) and index.
Keywords: Philosophy, Modern -- 19th century